KOSMOLOGI HINDU DALAM SANKHYA-YOGA - Putu Sri Marselinawati (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Cosmology is the science of the creation of the universe. Hindu cosmology is different from the common Cosmology studied by Western scientists, Hindu cosmology deliberately and consciously placing God as the beginning, middle, and end of cosmic existence, whereas Cosmology in general (the West) is not very important to locate and engage God, or if any, then God is only placed in a position that is not too central, and also only as the end to cover the impasse and confusion of his mind. Hindu cosmology explains that the universe is maintained over a period of time before it is melted. At the beginning of every cycle of the creation of the universe, Brahma-the first cosmic creature created. In the teachings of Sa?khya-Yoga states the existence of 25 elements in the process of creation, namely 5 Panca karmendriya, 5 PancaBudhindriya, 5 Panca Maha Bhuta, 5 Panca Tan Matra, Budhi, Ahamkara, Manah, citta, andkala. Hindu cosmology sees the creation of the universe or the cosmos beginning with God.From within the body or the content of God (hiranyah garbha) the universe is born, and theninto the womb of God (hence the garbha) also the universe will be restored. These 25 elementsalso reveal the process of creating bhuana alit or living organism one of the examples is human.